Pengetahuan Kewirausahaan Dengan Minat Berwirausaha Baby Spa Pada Mahasiswa Program Studi Sarjana Terapan Kebidanan - Syahida Khoirun Nisa; Finta Isti Kundarti; Eny Sendra; Rahajeng Siti Nur Rahmawati (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2026)
The increasing number of midwifery students graduating is not commensurate with the availability of formal employment opportunities, so an alternative is needed in the form of entrepreneurship development in the field of midwifery, one of which is through baby spa businesses. This study aims to analyze the relationship between the level of entrepreneurial knowledge and the interest in baby spa entrepreneurship among students of the Applied Undergraduate Study Program of Midwifery Kediri, Poltekkes Kemenkes Malang. This study is quantitative with a cross-sectional approach. The respondents were 45 final-year students from a total population of 50 people through simple random sampling. The research instrument was a questionnaire, while data analysis was based on Spearman Rank correlation. The results showed a significant relationship between entrepreneurial knowledge and interest in baby spa entrepreneurship (p = 0.014) with a correlation coefficient value of 0.362, indicating a positive relationship with low strength. This study confirms that the better the students' entrepreneurial knowledge, the more likely they are to start a baby spa business as an independent business in the health sector. Therefore, strengthening entrepreneurial competencies and integrating applied materials into the midwifery curriculum is very important to foster an entrepreneurial spirit from the educational period.